Trunk Extensor, Flexor and Lateral Flexor Endurance Time in sedentary workers aged 20-49 years - Wattana Jalayondeja (2018)
Objective: The purposes of this study were to 1) quantify trunk endurance times according to subjects’ age and sex; and 2) identify factors affecting the endurance times. Material and Method: Endurance times of sedentary workers aged 20-49 years were determined by an extensor endurance, a flexor endurance, and right and left side bridge (trunk lateral flexor) tests. Each test was performed once in random order with a resting period of 10 minutes between tests. Results: Of 137 workers, Two-way analysis of variance indicated that age had no effect on these 4 isometric trunk endurance tests. Sex had an effect on the extensor endurance test, and right and left side bridge tests. Females had longer endurance times than males for the trunk extensor muscle, whereas males had longer endurance times than females for right and left lateral flexor trunk muscles. Low negative but significant Pearson’s correlations (r = -0.233 to -0.377, p = 0.047 to 0.001) were found between extensor endurance times vs. body weight and abdominal skinfold thickness in both sexes. Only in males, both right and left side bridge endurance times correlated with abdominal skinfold thickness (r = -0.296 and r = -0.382, respectively, p < 0.05 both). Conclusion: Sex, weight and abdominal skinfold thickness factors should be considered when trunk muscle endurance is evaluated.